Rattini (Rodentia, Murinae) species relationships and involvement as reservoirs for Scrub Typhus : a comparative molecular cytogenetic gene expression approach - Badenhorst, Daleen (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD (Botany and Zoology))--Stellenbosch University, 2011.